Simulation Technique of Kinematic Processes in the Vehicle Steering Linkage - Chernenko, Sergii; Klimov, Eduard; Chernish, Andrii; Pavlenko, Olexandr; Kukhar, Volodymyr (International Journal of Engineering and Technology, 2018)
The results of the investigation of the turning kinematics of the steerable wheels of the KrAZ-7634NE off-road vehicle with a wheel formula 8x8 and two front steer axles are given. The theoretical relations between the steer angles of the steerable wheels on the basis of the scheme of double-axle steering turning of the vehicle are shown. The mathematical model of flat four-bar vehicle steering linkage is developed, it determines the relation between the steering linkage left and right steering arms turning angles at any turning radius of the vehicle. KrAZ-7634HE steering three-dimensional model was created and simulation technique of its work was carried out using Creo software. It has been shown that the flat steering linkage model provides sufficient accuracy of calculations in analysis of turning kinematics. The design data can be used for any vehicles that have a similar steering linkage, they allow to analyze the impact of the vehicle design parameters on the turning kinematics and optimize them. Further study of the impact of the kingpin inclinations on the steering linkage kinematic and power characteristics are required.Â Â